IMPROVING STUDENTS’ VOCABULARY IN DESCRIPTIVE TEXT BY USING CLIMBING UP THE LADDER GAME - Ningtias, Wahyu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbsractThis research was conducted to know how climbing the ladder game improved students’ vocabulary in descriptive text. It was conducted to solve students’ problems in meaning and spelling vocabularies along with students’ reading comprehension. It is a classroom action research on the seventh grade students in SMP N 8 Pontianak. The subjects of the research are students of GRADE VII D, numbering thirty five students. The research was done in three cycle. The datas were collected through observation checklist, field note, and written test in form of multiple choices test. The results indicate that climbing up the ladder game improved students’ vocabulary in recognizing the meaning of words and in spelling the meaning of words. Students’ improvement were proven by their mean scores which improved from 66.67 in the first cycle to 81 in the second cycle and 82.28 in thw third cycle. Therefore, the students achieved KKMscore in the second and third cycle which means students improved their vocabulary.Key words: vocabulary, climbing up the ladder game, descriptive text